Cyclic microwave-assisted synthesis of CuFeS2nanoparticles using biomolecules as sources of sulfur and complexing agent - Kamonwan Aup-Ngoen (2018)
Copper iron sulfide (CuFeS 2 ) nanoparticles were successfully synthesized by a 300 W cyclic microwave radiation, exposing onto ethylene glycol containing Cu(CH 3 COO) 2 , FeCl 3 · 6H 2 O or FeCl 2 · 4H 2 O and L-cysteine biomolecules. X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM), Raman spectrometry and X-ray photoelectron spectroscopy (XPS) revealed the presence of pure tetragonal chalcopyrite CuFeS 2 nanoparticles with valence states of Cu + , Fe 3+ and S 2- and four Raman shifts at 215.0-218.6, 280.2-281.4, 394.4-394.9 and 472.2-473.4 cm -1 . A formation mechanism of the products was also proposed according to the experimental results. © 2013 Elsevier B.V. All rights reserved.